(untitled) (Research, Society and Development, 2022)
The article that describes the dynamics of a flour mill in the Brazilian Amazon as a cultural activity of these peoples, is part of the project Multiculturalism and mathematical ideas in sociocultural practices: possibilities for the process of teaching mathematics in the state of Amazonas, developed within the scope of the Graduate Program of the Faculdade de Educação da Universidade Federal do Amazonas – PPGE/UFAM, whose objective is to understand how the mathematical ideas involved in the activities of these communities interfere in the teaching and learning process. It uses exploratory research as a methodology, with a qualitative approach in phenomenological processes. The results indicate that there are groups of teacher trainers, of teachers who work in elementary education and groups of academics developing Ethnomathematics, the teaching of mathematics through a cultural bias. It is expected that new fronts will be encouraged, and that meaningful and contextualized education will help the educational process of schools in the State of Amazonas, whose results enable the recognition of multiculturalism and mathematical ideas in sociocultural practices, for the process of teaching mathematics, to value the diversity, cultures rejected, forgotten, ignored by the advent of so-called “higher cultures” and bring to the discussion related topics.